Employability & Competences Innovative Curricula for New Professions - Boffo, Vanna; Fedeli , Monica (Studies on Adult Learning and Education, 2018)
The book is the final report of the researches, discussions, conversations around and about the Project PRIN Employability & Competences which took place on March 9th-‐11th, 2017 within an International Conference at the University of Florence. It was the final event of the project PRIN2012LATR9N which aims were: «to design innovative programs for higher education, to promote personalized and learner-centered teaching and learning, to build on job competencies, to value talents to create new work opportunities, to support young adults during their employment emergency, as a response to socio economic crisis and as a citizenship action». The research activities concerned the main phases of the students' academic life: career guidance upon entry, personalized teaching, career calling, professional vocation, profession building activities such as internships and work related experiences, and lastly job placement.